Religious Participation is Associated with Increases in Religious Social Support in a National Longitudinal Study of African Americans - Le, Daisy (Journal of religion and health, 2016)
This study reports on the association between religious beliefs and behaviors and the change in both general and religious social support using two waves of data from a national sample of African Americans. The Religion and Health in African Americans (RHIAA) study is a longitudinal telephone survey designed to examine relationships between various aspects of religious involvement and psychosocial factors over time. RHIAA participants were 3173 African American men (1281) and women (1892). A total of 1251 men (456) and women (795) participated in wave 2 of data collection. Baseline religious behaviors were associated with increased overall religious social support from baseline to wave 2 (p < .001) and with increased religious social support from baseline to wave 2 in each of the following religious social support subscales: emotional support received (p < .001), emotional support provided (p < .001), negative interaction (p < .001), and anticipated support (p < .001). Religious beliefs did not predict change in any type of support, and neither beliefs nor behaviors predicted change in general social support. African Americans who are active in faith communities showed increases in all types of religious social support, even the negative aspects, over a relatively modest longitudinal study period. This illustrates the strength of the church as a social network and the role that it plays in people’s lives.